Ekstrak Etanol Daun Jati Belanda (Guazuma ulmifolia Lamk) Memperbaiki Profil Lipid Tikus (Rattus norvegicus) Wistar Jantan Dislipidemia - Melita Hidajat; I Gusti Made Aman; Hendro Sukoco; Ferbian Milas Siswanto (Universitas Sulawesi Barat, 2019)
The purpose of this study was to prove that the administration of Jati (Guazuma ulmifolia Lamk) leaves extract improves the lipid profile of dyslipidemic male Wistar rats. Subjects were 20 rats (Rattus norvegicus), male, Wistar strain, dyslipidemia (total cholesterol ≥ 200 mg dl-1), aged 2 months old, weighing 180-200 grams. The control group (10 rats) were given a placebo of 3 ml aquadest (P0) and the treatment group was given extracts of the Jati (Guazuma ulmifolia Lamk) leaves extract of 25 mg kg-1 BW (P1). Before and after treatment for 14 days, total cholesterol, triglyceride, LDL, and HDL levels were examined. The results showed that in the P0 group there were no changes in total cholesterol, triglyceride, LDL, and HDL levels (p>0.05), whereas the P1 group experienced a decrease in total cholesterol, triglyceride and LDL levels (p<0.05) and an increase in HDL levels (p<0.05). The results of this study indicated that the Jati leaves extract was effective to improve the lipid profile of dyslipidemic rats. It was necessary to compare the effectiveness of Jati leaves extract with synthetic dyslipidemia drugs used in the community such as statin.